Proposição de estratégias para controle profilático e terapêutico da encefalite autoimune experimental baseadas no efeito imunorregulador da hsp65 - Pezavento, Sofia Fernanda Gonçalves Zorzella [UNESP] (2013)
This project was mainly based on the immunoregulatory property of the mycobacterial hsp65. The proposal of this work was to evaluate if a DNA vaccine containing the hsp65 mycobacterial gene (pVAXhsp65) could be used as a prophylactic or therapeutic strategy to control experimental autoimmune encephalomyelitis (EAE) development. In the first part of this investigation we demonstrated that mice previously vaccinated with pVAXhsp65 lost less body weight and presented lower clinical score. Clinical improvement was associated with lower production of IL-10 by spleen cell cultures stimulated with MOG or ConA. Comparative histopathological analysis revealed less inflammatory process in the lumbar spinal cord of previously vaccinated mice in comparison to EAE control group. The second approach was designed to evaluate the possible therapeutic effect of pVAXhsp65 on EAE development. Even though this vaccine was immunogenic for mice with EAE and also able to downmodulate the induction of cytokines by MOG, it was not able to decrease the clinical severity of the disease. Vaccination did not decrease intensity of the inflammatory process neither the frequency of regulatory T cells (Tregs) in the central nervous system (CNS). Finally, we investigated the contribution of the peripheral and local IL-17 production to acute and chronic EAE stages. Mice submitted to EAE induction presented an initial acute phase characterized by accentuated weight loss and high clinical score, followed by a partial recovery when the animals reached normal body weight and smaller clinical scores. Spleen cells stimulated with MOG produced significantly higher levels of IFN-g during the acute period whereas similar IL-17 levels were produced during both Abstract disease stages. CNS infiltrating cells stimulated with MOG produced similar amounts of IFN-g but IL-17 was produced only at the acute phase of EAE. The percentage of Foxp3+ Treg cells, at the spleen and the CNS, was...